The Principal's Leadership in Building a Culture of Educational Quality at SDIT Al-Kautsar Mokumoku - Muhamad Iqbal Wibisono; Sutrisno; Suwadi (Cendekia : Jurnal Pendidikan dan Keagamaan, 2026)
This study aims to analyze the principal's leadership in building a culture of educational quality at SDIT Al-Kautsar Mukomuko. It employed a descriptive qualitative method, with data collected through in-depth interviews, observation, and documentation. The principal and teachers served as research informants. Data were analyzed using the Miles and Huberman model, while source and method triangulation was used to establish trustworthiness. The findings show that the principal practices adaptive situational leadership by fostering collaboration among all members of the school community. The implementation strategies include improving the learning process, developing teacher competence, managing supervision, and applying standard operating procedures for educational quality. Supporting factors include the principal's commitment, teacher quality, and parental support, whereas the principal obstacle is limited physical infrastructure. The findings underscore the importance of collaborative leadership and continuous evaluation in institutionalizing a culture of educational quality.